The role of the police in the effort to take action against the criminal act of cockfighting gambling in the legal territory of buleleng resort police (case study in Banyuning Village) - Komang Yudiani; Made Sugi Hartono; I Nengah Suastika; Ni Putu Ega Parwati (Priviet Social Sciences Journal, 2026)
This study aims to analyze law enforcement efforts against cockfighting gambling (Tajen) in Banyuning Village, Singaraja District, Buleleng Regency, and the obstacles encountered. Using a qualitative descriptive approach, primary data were collected through interviews with police officers, village officials, community leaders, and related actors. The results indicate that the Buleleng Police Resort has implemented preemptive, preventive, and repressive measures, but their effectiveness remains limited. Preemptive efforts through community education by Bhabinkamtibmas are not systematic, preventive patrols struggle to reach arenas located in narrow alleys, and repressive actions are influenced by reactive attitudes and discretionary decisions without the prosecution of key actors. Law enforcement obstacles are shaped by internal factors, such as a police organizational culture that tends to wait for reports, and external factors, including community economic dependence on Tajen, environmental conditions that facilitate offenders, and cultural beliefs that blur the line between rituals and gambling. This study recommends strengthening synergy among stakeholders, enhancing patrols in vulnerable areas, and improving environmental management and customary norms to reinforce law enforcement.